Baseline biomarker (tau PET) characteristics from TANGO: A phase 2 trial of gosuranemab (BIIB092) in early Alzheimer's disease. (December 2021) - Racine, Annie M.; Rajagovindan, Raj; Collins, Jessica A.; Kong, Jessica; Li, Yumeng; O'Gorman, John; Jones, Stephanie; Graham, Danielle; Ratti, Elena; Shulman, Melanie
Abstract: Background: Gosuranemab is a humanized monoclonal antibody that is hypothesized to neutralize extracellular tau and prevent the trans‐neuronal propagation of tau pathology across the brain. The TANGO study is an ongoing randomized, placebo‐controlled, global Phase 2 study evaluating safety and clinical efficacy of gosuranemab in individuals diagnosed with mild cognitive impairment (MCI) due to Alzheimer's disease (AD) or mild AD dementia. The TANGO study included two biomarker sub‐studies: cerebrospinal fluid (CSF) sub‐study and Tau positron emission tomography (PET) sub‐study; the baseline characteristics of the Tau PET sub‐study are described below. Method: TANGO enrolled 654 individuals aged 50‐80 years, diagnosed with MCI or mild AD, who were amyloid positive as assessed by amyloid PET or CSF testing. Approximately 350 patients enrolled in the longitudinal 18F‐MK‐6240 Tau PET sub‐study. Randomization was stratified by biomarker sub‐study participation among other factors. Baseline standardized uptake value ratio (SUVR) was measured in composite brain regions of interest (ROIs) corresponding to Braak I‐II, Braak III‐IV, and Braak V‐VI regions using superior‐eroded cerebellum as the reference region. Tau extent (percentage of supra‐threshold voxels within an ROI relative to reference region), an exploratory measure of the spatial extent of 18F‐MK‐6240 binding, was also investigated. Result: The baseline demographics of the Tau PET sub‐study population were consistent with the overall TANGO study population including clinical stage (MCI vs. mild AD), age, gender, APOE4, and clinical scores. At baseline, average SUVR (±SD) was 1.92±0.6 in Braak I‐II, 1.90±0.7 in Braak III‐IV and 1.75±0.8 in Braak V‐VI composite ROIs. The Braak composite SUVRs were positively associated with disease stage (i.e. higher SUVR with increasing disease severity). Exploratory analyses of extent were supportive of the SUVR results. Conclusion: At study baseline, tau SUVR was highest in Braak I‐II, followed by Braak III‐IV, then Braak V‐VI. Cross‐sectionally, higher tau PET SUVR was associated with increasing disease severity and worse clinical scores, as expected. The TANGO Tau PET sub‐study will aid our understanding of gosuranemab's effect on tau pathology and further inform on the value of tau PET in clinical trials.